Arctic and subarctic construction : runway and road design. - United States. Army. Corps of Engineers. ([Washington, D.C.] : Dept. of the Army, Corps of Engineers, Office of the Chief of Engineers, 1954)
"Superseding in part Pt. XII, Chap. 7, Oct. 46." "October 1954." Cover title. Includes bibliographical references. Mode of access: Internet.